Mite Infestation on Rattus tanezum rats in southwest China concerning risk models - Liu, Ru-Jin; Guo, Xian-Guo; Peng, Pei-Ying; Lv, Yan; Yin, Peng-Wu; Song, Wen-Yu; Xiang, Rong; Chen, Yan-Ling; Li, Bei; Jin, Dao-Chao (Frontiers in Veterinary Science, 2025)
ObjectiveThe Asian house rat (Rattus tanezumi) is an important infectious source and reservoir host for many zoonotic diseases, and its associated mites (chigger mites and gamasid mites) can act as vectors for these diseases. The present study aimed to elucidate the infestation patterns and related ecology of the mites on the body surface of R. tanezumi in southwest China and explore relevant risk models.MethodsField surveys and taxonomic identification of the mites were conducted across five provincial regions in southwest China between 2001 and 2022. The constituent ratio (Cr), prevalence (Pm), mean abundance (MA), and mean intensity (MI) were calculated to reflect the mite infestation status. The species richness index (Mf), Shannon–Wiener diversity index (H´), Pielou’s evenness (E), and Simpson’s dominance index (D) were used to analyze the mite communities. A multiple logistic regression model was employed to identify potential risk factors associated with the mite infestation. The “corrplot” R software (version 4.3.1) package was used to analyze interspecific relationships among some mite species.ResultsA total of 75,023 mites were collected from 3,114 R. tanezumi rats, representing 12 families, 46 genera, and 252 species. Among these, 173 were the chigger mite species and 79 were the gamasid mite species. The species richness and community diversity of the chigger mites were higher than those of the gamasid mites, but the infestation indexes of the gamasid mites on the rats were higher than those of the chigger mites. Several vector mite species co-existed on R. tanezumi, with Laelaps nuttalli, L. echidninus, and Leptotrombidium deliense identified as the three dominant mite species, exhibiting high infestation indexes. The multiple logistic regression analysis showed that the mite infestation was influenced by a series of environmental factors and host-related factors (potential risk factors), with temperature and relative humidity identified as the most important risk factors. The impact of these potential risk factors on the infestation of a single mite group (chigger mites or gamasid mites) was different from the impact on the co-infestation of both mite groups together. Based on the logistic regression analysis, three predictive models were developed to predict the risk probability of each R. tanezumi rat being infested with chigger mites alone, gamasid mites alone, and both mite groups together. A positive correlation existed between any two of the following species: L. deliense, L. rubellum, and L. imphalum.ConclusionRattus tanezumi rats are highly susceptible to mite infestation, hosting a variety of mite species and multiple vector mite species. The presence of multiple vector mite species on these rats increases the potential risk of transmission and persistence of related zoonotic diseases. A series of environmental factors and host factors, especially temperature and relative humidity, can influence mite infestation. The predictive models developed can estimate the likelihood of each rat being infested with mites. Some mite species show a preference for co-existing on R. tanezumi.